2000
DOI: 10.1007/3-540-46419-0_26
|View full text |Cite
|
Sign up to set email alerts
|

Salsa: Combining Constraint Solvers with BDDs for Automatic Invariant Checking

Abstract: Salsa is an invariant checker for specifications in SAL (the SCR Abstract Language). To establish a formula as an invariant without any user guidance, Salsa carries out an induction proof that utilizes tightly integrated decision procedures, currently a combination of BDD algorithms and a constraint solver for integer linear arithmetic, for discharging the verification conditions. The user interface of Salsa is designed to mimic the interfaces of model checkers; i.e., given a formula and a system description, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…This initial study has shown that it is relatively straightforward to associate safety properties with generic modules that implement such architectural patterns. Proofs of these properties were carried out using the standard induction technique [7] using an assumption/guarantee proof system for compositional reasoning similar to [13]. Although we have automated the proofs of safety properties for concrete instances of an architectural pattern, an open problem is to develop automatic proof strategies for the generic case.…”
Section: Architectural Patternsmentioning
confidence: 99%
“…This initial study has shown that it is relatively straightforward to associate safety properties with generic modules that implement such architectural patterns. Proofs of these properties were carried out using the standard induction technique [7] using an assumption/guarantee proof system for compositional reasoning similar to [13]. Although we have automated the proofs of safety properties for concrete instances of an architectural pattern, an open problem is to develop automatic proof strategies for the generic case.…”
Section: Architectural Patternsmentioning
confidence: 99%
“…The prototype Sage toolchain includes the Sage prototype tool set, sol2sal compiler, Salsa property checker [6], Sol compiler [4], and SINS middleware [5] which provides an execution environment for Sage agents. The prototype Sage tool set comprises a set of plug-ins to the Eclipse IDE (integrated development environment) and a set of external programs and scripts.…”
Section: Exercising the Sage Tool Setmentioning
confidence: 99%
“…The SCR toolset [10] provides a user-friendly approach to writing requirements specifications and a suite of analysis tools for analyzing them. The toolset includes a consistency checker [13], a simulator [12], a model checker [11], theorem provers [2,4], and an invariant generator [15,17].…”
Section: Introductionmentioning
confidence: 99%